2019
DOI: 10.1039/c9ra04736k
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, optical and thermoelectric properties of Fe2ZrP compound determined via first-principles calculations

Abstract: In this study, based on the density functional theory and semi-classical Boltzmann transport theory, we investigated the structural, thermoelectric, optical and phononic properties of the Fe2ZrP compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 71 publications
(98 reference statements)
2
10
0
Order By: Relevance
“…Our calculated value of the lattice parameter is quite comparable with the 6.00 Ǻ, 77 obtained by the Sanvito et al using the Vienna Ab initio Simulation Package (VASP) code. The similar calculations are also performed to obtain total energy in the paramagnetic and FM phases and it is found that total energy is minimum in the FM phase like the other HAs 44,45,52,62,67 . The ground state properties like bulk modulus, B o and its first order pressure derivative, B o ′ are also calculated using Equation ) and their values are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our calculated value of the lattice parameter is quite comparable with the 6.00 Ǻ, 77 obtained by the Sanvito et al using the Vienna Ab initio Simulation Package (VASP) code. The similar calculations are also performed to obtain total energy in the paramagnetic and FM phases and it is found that total energy is minimum in the FM phase like the other HAs 44,45,52,62,67 . The ground state properties like bulk modulus, B o and its first order pressure derivative, B o ′ are also calculated using Equation ) and their values are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, novel HAs are being studied theoretically due to fast computational facilities to predict their structural, electronic states, spin orientation, magnetic moment, bonding, mechanical, thermodynamic and thermoelectric properties. The recent first principles studies on some Co‐based, 44‐49 Fe‐based, 36,38,50‐53 Zr‐based 54‐56 and Ti‐based with new dimensions 57 HAs showed keen interest. As far as the research of Mn‐based full HAs is concerned, Mn 2 VAl was found the first full HA investigated in theoretical 58‐60 and experimental 61 research.…”
Section: Introductionmentioning
confidence: 99%
“…The highest values of the S are according to the band degeneracy, in accordance with which the effective mass directly relates to band degeneration ðm* ¼ N V 2=3 m * b Þ here N V and m * b denote the effective mass related to a single valley degeneracy that can increase. Likewise, the effect of the S on the effective mass is illustrated by the Mott relation shown below in eqn (8). As a result, the increase in S is due to the decrease of carrier concentration.…”
Section: Thermoelectric Propertiesmentioning
confidence: 96%
“…6 The total spin magnetic moment of FeCr-based QHA is found to be 1.00 to 4.00m B per formula unit conrms that the alloys are halfmetallic ferromagnets in nature. 7 In recent years, half metallic, thermoelectric and optical properties in Heusler alloys and perovskite have received a lot of attention from researcher, [8][9][10][11] XTiCl 3 (X = Rb, Cs), 12 FeCrMnSb, 13 FeNbScZ (Z = Al, Ga, Ge, Si), 14 FeCrRuZ (Z = Al, Ga, In & Si), 15 Fe 2 TaZ (Z = Al, Ga & In), 16 Fe 2 VAl, 17 Fe 2 TiZ (Z = Ga, Ge, As, In, Sn & Sb), 18 Fe 2 -TiSi, Fe 2 TiGe and Fe 2 ZrSi, 19 Fe 2 CrSb, 20 Fe 2 TaZ (Z = Al, Ga, In), 21 FeZrTiZ (Z = Si, Sn, Pb), 22 FeCrRuSi, 23 CoZrCrZ (Z = Al, Ga, In), 24 Mn 2 MgGe, 25 XRuCrZ (X = Co, Ni, Rh and Pd; Z = Si and Ge), 26 XCaB (X = Li, Na, K and Rb), 27 ZrTiRhZ (Z = Ge, Sn), 28 CoFeVSb, 29 YFeCrZ (Z = Al, Sb & Sn), 30 CoFeXSn (X = Ru, Zr, Hf & Ta), 31 CoFeRGa (R = Ti, V, Cr, Mn, Cu and Nb), 32 MNiSn 33 Mn 2 ZrX (X = Ge, Si). 34 Alloys have been discovered to be halfmetallic.…”
Section: Introductionmentioning
confidence: 99%
“…where Ω is the volume of the unit cell, e indicates electronic charge, ε 0 signifies permittivity of free space, u defines the polarization of the incident electric field, r and k are the vectors in the real and reciprocal lattice, respectively, and Ψ v k and Ψ c k are the valence band and conduction band wavefunctions at k point corresponding to energies E v k and E c k , respectively. The ε 1 ðωÞ and ε 2 ðωÞ parameters are related to each other using the famous Kramer-Kronig transformations [35][36][37]. These relations are used to obtain the real part of dielectric function from the imaginary part.…”
Section: Optical Propertiesmentioning
confidence: 99%